GAP Generation: Perbedaan Perspektif dan Gaya Komunikasi - Lestari, Aghnia Dian; Yulianita, Neni (JURNAL KOMUNIKATIO, 2025)
With the rapid advancement of technology and social change, how people from different generations interact and communicate has been transformed. Higher education is dominated by a multigenerational environment. This study aims to explore the differences in perspectives and communication patterns between generations, namely Generation X, Y (Millennials), and Z. This study uses a qualitative method with a phenomenological approach to explore the differences in perspectives and communication patterns between generations. This research uses a qualitative method with a phenomenological approach to explore how different values, experiences, and use of technology affect social and academic interactions among students. The results of this study show differences in the way of communicating in each generation, with Generation X tending to value communication more with face-to-face and formal communication, while Generation Y and Z prefer digital and informal communication. However, differences in values, experiences, and access to technology shape communication patterns in the classroom or student organization activities between generations. Gap generation is prone to conflict, such as gaps in age, appearance and lifestyle, perception, experience, behavior, and communication. It is important to build effective communication and inclusion across generations to form an understanding and perspective in creating harmonious relationships, especially in a diverse academic environment.